Legal Protection for Creditors in Relation to Unregistered Fiduciary Security - Nurul Fitria Zulmi; Muhammad Insa Ansari; Muhammad Ya’kub Aiyub Kadir (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Law Number 42 of 1999 concerning Fiduciary Security requires every object encumbered with fiduciary security to be registered at the Fiduciary Registration Office. Such registration constitutes a constitutive requirement for the establishment of proprietary rights that grant creditors preferential status and executorial authority. Nevertheless, in practice, unregistered fiduciary security agreements are still frequently encountered, giving rise to legal issues concerning creditor protection and legal standing. This study aims to examine the forms of legal protection available to creditors, the legal consequences of unregistered fiduciary security, and the implications of Constitutional Court Decision Number 18/PUU-XVII/2019 on creditor protection. This research employs a normative legal method using statutory and conceptual approaches. The data were obtained from primary, secondary, and tertiary legal materials, which were subsequently analyzed qualitatively. The findings indicate that legal protection for creditors is provided through notarial deeds, fiduciary registration, and fiduciary certificates that establish preferential rights and executorial power. In contrast, unregistered fiduciary security does not create proprietary rights, resulting in creditors being positioned merely as concurrent creditors under Articles 1131 and 1132 of the Indonesian Civil Code. This study recommends that the government improve the effectiveness of the fiduciary registration system through procedural simplification and the strengthening of electronic administrative systems. Furthermore, financing institutions and banks should consistently register fiduciary security in order to ensure optimal legal certainty and protection.